2015
DOI: 10.33549/physiolres.933195
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intima-Media Thickness of Carotid Arteries With Remnant Lipoproteins in Men and Women

Abstract: The subclass of triglyceride-rich lipoproteins -remnant-like particles (RLP) seems to be strong and independent risk factor for cardiovascular disease. We evaluated the role of RLP and other risk factors (RF) with sonographically measured intimamedia thickness of carotid arteries (IMT CCA) in a cohort of Czech population including women defined according to the time after menopause. We investigated relation of IMT CCA to age, weight, central obesity, plasma lipids including remnant-like particles cholesterol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…However, we found no association between cEMT and TG. Our result is consistent with epidemiological studies that found TG to be an independent risk factor for cardiovascular diseases in terms of cIMT (Pitha et al , ). High blood pressure is a major cause of subclinical atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…However, we found no association between cEMT and TG. Our result is consistent with epidemiological studies that found TG to be an independent risk factor for cardiovascular diseases in terms of cIMT (Pitha et al , ). High blood pressure is a major cause of subclinical atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…The available literature data also indicates that there is a close relationship not only between serum levels of total cholesterol, but also between individual lipid fractions and IMC thickness (1014) . Kunicka et al .…”
Section: Discussionmentioning
confidence: 94%
“…It was proved, that AIP values significantly increase with increasing cardiovascular risk. AIP was the best predictor of positive findings (Piťha et al, 2015). AIP was also a highly sensitive marker of differences in lipoprotein profiles in families of patients with premature myocardial infarction and in control families.…”
Section: Risk In Disease Conditionsmentioning
confidence: 85%